Colloidal organization - Ōkubo, Tsuneo (Elsevier, 2015)
Colloidal Organization presents a chemical and physical study on colloidal organization phenomena including equilibrium systems such as colloidal crystallization, drying patterns as an example of a dissipative system and similar sized aggregation. This book outlines the fundamental science behind colloid and surface chemistry and the findings from the author's own laboratory. The text goes on to discuss in-depth colloidal crystallization, gel crystallization, drying dissipative structures of solutions, suspensions and gels, and similar-sized aggregates from nanosized particles. Special emphasis is given to the important role of electrical double layers in colloidal suspension. Written for students, scientists and researchers both in academia and industry and chemical engineers working in the fields of colloid and surface chemistry, biological chemistry, physical chemistry, physics, chemical technology, and polymer technology this book will help them to exploit recent developments recognizing the potential applications of colloid science in enhancing the efficiency of their processes or the quality and range of their products.